Characterization of Imidazoline Receptors in Blood Vessels for the Development of Antihypertensive Agents. (3rd April 2014) - Chen, Mei-Fen; Tsai, Jo-Ting; Chen, Li-Jen; Wu, Tung-Pi; Yang, Jia-Jang; Yin, Li-Te; Yang, Yu-lin; Chiang, Tai-An; Lu, Han-Lin; Wu, Ming-Chang
Abstract : It has been indicated that activation of peripheral imidazoline I2 -receptor (I-2R) may reduce the blood pressure in spontaneously hypertensive rats (SHRs). Also, guanidinium derivatives show the ability to activate imidazoline receptors. Thus, it is of special interest to characterize the I-2R using guanidinium derivatives in blood vessels for development of antihypertensive agent(s). Six guanidinium derivatives including agmatine, amiloride, aminoguanidine, allantoin, canavanine, and metformin were applied in this study. Western blot analysis was used for detecting the expression of imidazoline receptor in tissues of Wistar rats. The isometric tension of aortic rings isolated from male rats was also estimated. The expression of imidazoline receptor on rat aorta was identified. However, guanidinium derivatives for detection of aortic relaxation were not observed except agmatine and amiloride which induced a marked relaxation in isolated aortic rings precontracted with phenylephrine or KCl. Both relaxations induced by agmatine and amiloride were attenuated by glibenclamide at concentration enough to block ATP-sensitive potassium (K ATP ) channels. Meanwhile, only agmatine-induced relaxation was abolished by BU224, a selective antagonist of imidazoline I2 -receptors. Taken together, we suggest that agmatine can induce vascular relaxation through activation of peripheral imidazoline I2 -receptor to open K ATP channels. Thus, agmatine-like compound has the potential to develop as a new therapeutic agent for hypertension in the future.